Efficient dehydration and recovery of ionic liquid after lignocellulosic processing using pervaporation - Jian Sun; Jian Shi; N. V. S. N. Murthy Konda; Dan Campos; Dajiang Liu; Stuart Nemser; Julia Shamshina; Tanmoy Dutta; Paula Berton; Gabriela Gurau; Robin D. Rogers; Blake A. Simmons; et al. (Biotechnology for Biofuels, 2017)
Abstract Background Biomass pretreatment using certain ionic liquids (ILs) is very efficient, generally producing a substrate that is amenable to saccharification with fermentable sugar yields approaching theoretical limits. Although promising, several challenges must be addressed before an IL pretreatment technology can become commercially viable. One of the most significant challenges is the affordable and scalable recovery and recycle of the IL itself. Pervaporation (PV) is a highly selective and scalable membrane separation process for quantitatively recovering volatile solutes or solvents directly from non-volatile solvents that could prove more versatile for IL dehydration. Results We evaluated a commercially available PV system for IL dehydration and recycling as part of an integrated IL pretreatment process using 1-ethyl-3-methylimidazolium acetate ([C2C1Im][OAc]) that has been proven to be very effective as a biomass pretreatment solvent. Separation factors as high as 1500 were observed. We demonstrate that >99.9 wt% [C2C1Im][OAc] can be recovered from aqueous solution (≤20 wt% IL) and recycled five times. A preliminary technoeconomic analysis validated the promising role of PV in improving overall biorefinery process economics, especially in the case where other IL recovery technologies might lead to significant losses. Conclusions These findings establish the foundation for further development of PV as an effective method of recovering and recycling ILs using a commercially viable process technology.